2019
DOI: 10.1155/2019/3702649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Multihollow Surface Dielectric Barrier Discharge Plasma on Chemical and Antioxidant Properties of Peanut

Abstract: An experiment was conducted to investigate the effects of atmospheric pressure plasma generated by multihollow surface dielectric barrier discharge on chemical and antioxidant properties of peanut. Multihollow surface dielectric barrier discharge is a novel plasma device applicable in food industry applications due to the capacity of the generated plasma to treat the surface of food without changing the quality. Peanut seeds were exposed to the multihollow plasma for different plasma power (10–40 W), air flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 67 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…Hence, there are different areas of their potential application. Recently reported plasmas [18][19][20][21][22][23][24] resemble LPGP neither in the methods of their generation nor in their character.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, there are different areas of their potential application. Recently reported plasmas [18][19][20][21][22][23][24] resemble LPGP neither in the methods of their generation nor in their character.…”
Section: Introductionmentioning
confidence: 99%
“…Multi-hollow surface dielectric barrier discharge (MSDBD) has been successfully tested and investigated for plasma treatment of materials like glass and silicon [ 25 ], polycarbonate polymer [ 26 ], and food processing [ 27 , 28 ]. This ambient air plasma source offers the capability of a remote plasma modification or decontamination of materials at enlarged distances [ 18 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The electrical characteristics and temperature measurements of MSDBD in different gases and at a wide gas flow range [ 25 , 26 , 27 , 28 ] were essential to understanding its safe operation and potential application. The main advantage of the robust MSDBD electrode system is its capability to withstand high-temperature loads.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid oxidation and increased rancidity have been previously reported, depending on the matrix and plasma conditions applied (Gavahian et al, 2018;Lee et al, 2018;Pérez-Andrés et al, 2020). According to Gebremical et al (2019), an increase of FFA in peanuts was observed with a power of 36 W in a DBD plasma. Also, Yepez and Keener (2016) reported a significant increment of different FFA (C18:1, n-9; C18:0; C16:0) after an extended exposure of 1-12 h of soybean oil to a plasma powered with 90 kV.…”
Section: Quantification Of Free Fatty Acidsmentioning
confidence: 95%